2007
DOI: 10.4012/dmj.26.906
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical Properties and Surface Degradation of Self-adhesive Resin Cements

Abstract: This study sought to evaluate the pH value, film thickness, filler particle percentage, and morphological changes of selfadhesive resin luting cements. Products tested were G-Cem, Maxcem, Smart Cem, and RelyX™ Unicem. Cement pH was measured with pH test paper. Filler particle percentage was calculated after cement samples were incinerated at 750℃. To test film thickness, mixed cements were placed between two glass plates and compressed using a loading device. For morphological changes, specimen surfaces were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
101
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 34 publications
2
101
0
11
Order By: Relevance
“…In this study, RXU revealed significantly less shrinkage strains when self-cured compared to dual-cured setting. In the study by Han [22] , the pH value for RXU was 7.0 48 hours after cementation, while GCM (pH 3.6) and SMC (pH 4.0) maintained in a significant lower pH level. Similar results have been shown in a study by Saskalauskaite [26].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In this study, RXU revealed significantly less shrinkage strains when self-cured compared to dual-cured setting. In the study by Han [22] , the pH value for RXU was 7.0 48 hours after cementation, while GCM (pH 3.6) and SMC (pH 4.0) maintained in a significant lower pH level. Similar results have been shown in a study by Saskalauskaite [26].…”
Section: Discussionmentioning
confidence: 94%
“…At conventional resin cements during dentin pre-treatment the dentin tubules are opened and a hybrid layer with resin tags into the dentin can be observed [10] or the smear layer is merely altered and the intertubular collagen only mild demineralised by the bonding agent as in the control group PAN [10]. Measurements of pH values of RXU and GCM after light curing showed values of 5.0 or less [22]. Therefore this cements seem to have technically a potential of decalcification of the dentin.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Acid materials retain some degree of hydrophilicity that leaves them prone to capture water, expand and degrade their structural matrices 14 . For cements RelyXUnicem and G-Cem, a work published by Han et al 15 confirm an increase in their pH within 48h following photoactivation.…”
Section: Discussionmentioning
confidence: 70%